Ektor UMKM di Indonesia:“ Profil, Masalah, Peran Penting, dan Strategi Pengembangan UMKM ‘’ - Dwi Anggraini; Zhafirah Salsabila (JIKEM: Jurnal Ilmu Komputer, Ekonomi dan Manajemen, 2023)
Indonesia has great potential to become a country with a large-scale economy in the world thanks to its natural resources, human resources, macroeconomic stability and conducive investment climate. However, serious social problems such as poverty and unemployment still exist. Efforts to overcome this social problem through empowering (UMKM) are an important step, with the development of information technology, infrastructure and entrepreneurship education. This can help increase economic growth, reduce poverty, and create competent entrepreneurs. The conclusion of this paper is that the strong commitment from the government has encouraged the development of (UMKM), which have good prospects for further empowerment. This interest is related to the less than satisfactory national economic conditions in recent years, which are partly caused by the financial and non-financial problems faced by (UMKM). Community welfare is very important in an economic context, and (UMKM) play a role in meeting people's daily needs, such as clothing and food. This research aims to understand the role of (UMKM) in improving community welfare, which in turn can support the country's economic growth and development. Apart from that, legal aspects also support efforts to realize community welfare through regulations aimed at supporting (UMKM).